The 5′-Terminal Nucleotide Sequence of Galactose Messenger Ribonucleic Acid of Escherichia coli - Musso, Richard E. (1974)
The 5′-terminal sequence of mRNA from the galactose operon of E. coli has been determined. gal RNA is synthesized in vitro by means of a kinetically controlled purified transcription system and is isolated by a two-step RNA·DNA hybridization scheme. The following sequence of the first 77 nucleotides has been deduced by analysis of oligonucleotides produced by digestion with T(1), pancreatic, and carboxymethylated pancreatic ribonucleases: ppA-U-A-C-C-A-U-A-A-G-C-C-U-A-A-U-G-G-A-G-C-G-A-A-U-U-A-U-G-A-G-A-G-U-U-C-U-G-G-U-U-A-C-C-G-G-U-G-G-U-A-G-C-G-G-U-U-A-C-A-U-U-G-G-A-A-G-U-C-A-U-A-C-C-U-G-U. Residues 27-77 correspond to the amino terminal 17 amino acids of UDPgalactose 4-epimerase (EC 5.1.3.2), the protein specified by the promoter-proximal structural gene of the operon. A self-complementary sequence occurs near the 5′ terminus; 12 of 15 nucleotides between residues 4 and 18 are symmetrically located about position 11. The sequence of residues 22-33 closely resembles part of the lactose operator sequence reported previously [Gilbert, W. & Maxam, A. (1973) Proc. Nat. Acad. Sci. USA 70, 3581-3584].